Control De Calidad De La Producción De Banano De La Hacienda La Julia - Terranova Mayorga, Mirtha Angelica (2018)
he present study on the Control of the Quality of the Banana Production of the Hacienda la Julia that is located in the Babahoyo canton, 4 km away and with an extension of 1059 ha of Banana. And approximately with a production of 2600 boxes per hectare / year. The Hacienda la Julia was created in 1988 by Luis Adolfo Noboa Naranjo, considered the richest man in Ecuador in the 20th century. Nowadays, it is owned by his son Álvaro Fernando Noboa Pontoon, owner of the exporter Noboa.